Development of Local Government Human Resources in The Perspective of Work Professionalism - Yosa, Yosa; Nuryadi, Iman; Sukari, Sukari; Ridwan, Iwan Yusuf; Sutrisno, Endang; Khumayah, Siti (Politeknik Siber Cerdika Internasional, 2024)
The development of Human Resources (HR) in Regional Government (Pemda) is crucial for effective and responsive governance. This study delves into government policies on HR development for local government apparatus from a professionalism perspective. Using a qualitative approach and case study method, the research analyzes field data, documents, and interviews with decision-makers like regional apparatus heads. Data was collected through in-depth interviews, policy document analysis, and direct observation. The findings reveal that despite supportive policies, the professionalism of local government officials remains below expectations. Challenges such as budget constraints, limited managerial capacity, and employee resistance to change hinder the effectiveness of HR development policies. The gap between HR development programs and work professionalism highlights the need for better policy supervision, evaluation mechanisms, and increased stakeholder participation in decision-making. This study underscores the necessity of strong political commitment and a holistic approach to achieve desired HR development outcomes in Regional Government.